Fish Bone that Hooked an Adenoma-Primary Hyperparathyroidism - Thomas, Sharon C; K, Rajalekshmi; John, Anulekha Mary; Joy, Jibily; Kurian, John S; Thomas, Rony; Chacko, Leslie Jacob (Journal of Pharmacy Practice and Community Medicine)
Primary hyperparathyroidism (PHPT) usually presents with one of the classical symptoms of hypercalcemia – painful bones, psychic moans, abdominal groans or renal stones. It is well known that many a times PHPT can be asymptomatic. Asymptomatic parathyroid disease is identified on screening, when calcium is found elevated or when bone density is found to be unusually low. Impacted fish bone being a reason for neck imaging and thereby leading on to a diagnosis of PHPT is uncommon. Here we present the unusual way in which a left inferior parathyroid adenoma was diagnosed in a 51 year old lady.
Keywords: Parathyroid adenoma; Hypercalcemia; Hyperparathyroidism; Foreign body; Fishbone